2017
DOI: 10.1002/jcp.26104
|View full text |Cite
|
Sign up to set email alerts
|

Primary familial brain calcification with a novel SLC20A2 mutation: Analysis of PiT‐2 expression and localization

Abstract: Primary familial brain calcification (PFBC) is an autosomal dominant rare disorder characterized by bilateral and symmetric brain calcifications, and neuropsychiatric manifestations. Four genes have been linked to PFBC: SLC20A2, PDGFRB, PDGFB, and XPR1. In this study, we report molecular and clinical data of a PFBC patient carrying a novel SLC20A2 mutation and we investigate the impact of the mutation on PiT-2 expression and function. Sanger sequencing of SLC20A2, PDGFRB, PDGFB, XPR1 led to the identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…3F ). Patients with primary familial brain calcification disease carry a novel duplication of 626 WFVT in h PiT, which corresponds to 378 WLLI in Tm PiT ( 28 ). This mutation does not affect expression of h PiT, but it does alter subcellular protein localization and impairs Pi internalization ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…3F ). Patients with primary familial brain calcification disease carry a novel duplication of 626 WFVT in h PiT, which corresponds to 378 WLLI in Tm PiT ( 28 ). This mutation does not affect expression of h PiT, but it does alter subcellular protein localization and impairs Pi internalization ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…Taglia et al . have shown that in PiT-2 trp626_629dup patients, PiT-2 does not migrate to the membrane and is abnormally localized to the nucleus 37 . Yamada et al .…”
Section: Discussionmentioning
confidence: 99%
“…Some of these mutations are loss‐of‐function mutations, in which improperly produced proteins are unable to act as a phosphate transporter (Hsu et al, 2013; López‐Sánchez et al, 2020). The precipitation of calcium phosphate in brain tissue that is detected in PFBC results from the accumulation of phosphate ions in the cell through the ineffective export and retention of Pi in the extracellular space (Anheim et al, 2016; Taglia et al, 2018). In the present study, we noticed a slightly different tendency.…”
Section: Discussionmentioning
confidence: 99%